The Implementation of People Analytics to Enhance Employee Well-Being in the Era of Hybrid Work - Mahendra, Putra; Amelia, Rizky (Universitas Sains dan Teknologi Komputer, 2026)
The digital transformation and the adoption of hybrid workplaces in the wake of the pandemic have reshaped the workplace landscape and, at the same time, posed new threats to employees' well-being, including digital stress, emotional burnout, and reduced social interaction. In this scenario, People Analytics is a vital, data-driven, and real-time method for recognizing employee behavior, participation, and well-being. The present research aims to examine the effect of People Analytics adoption on employee well-being in the hybrid work era, with employee engagement as a mediator and data ethics as a moderator. A quantitative explanatory approach is taken for the study, and 400 participants from the service and technology sectors in Indonesia are involved. The data is analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to reveal relationships among variables. The results show that People Analytics has a positive and significant effect on employee well-being (β = 0.527; p < 0.001). Employee engagement partially mediates this relationship, and data ethics further strengthens it. The uniqueness of this study lies in the creation of the People Analytics for Well-being (PAW) Framework, which integrates well-being, engagement, and data ethics dimensions within human resource analytics systems. This study theoretically broadens the discussion of Human Resource Analytics and, in practice, offers ethical guidelines for organizations to balance productivity and employee well-being in the hybrid work era.